The National Planning Policy Framework: A Response to the Joe Flatman and Dominic Perring Article - Duncan McCallum (Papers from the Institute of Archaeology, 2013)
In early 2010, the rumours circulating shortly before the final publication of PPS5 that all planning policy was likely to be combined into a single document caused a degree of nervousness among heritage organisations. The previous government decided to go ahead and publish PPS5 rather than cancel its publication and consider heritage issues afresh alongside all other planning policy issue. With the benefit of hindsight, this proved to be very helpful for heritage. However, the goal of a unified policy document was made clear shortly afterwards. Fortunately, by the time work started on it in earnest, PPS5 had had just about enough ‘bedding down’ time to be seen as a broadly successful document.
Keywords: National Planning Policy Framework; planning; development